Ayurvedic perspective on osteoarthritis: management and outcomes: a case report - C. B., Savitha; T. C., Marikutty (International Journal of Research in Medical Sciences, 2025)
Osteoarthritis is a foremost health problem considering its associated disability and impact on the quality of life. It is a leading cause of disability in elderly people. This is a case of a 74-years-old female who presented with multiple joint pains, namely, right shoulder joint, left hip joint, numbness over both feet and gastric discomfort and was admitted to the Kayachikitsa IPD of Vaidyaratnam Ayurveda College Hospital on 02/04/2025. She has been diagnosed with a case of osteoarthritis (Sandhigatavata) based on ACR criteria, including the clinical presentation, physical examination, laboratory tests and Kellgren’s radiographic scale. The patient underwent treatment based on the principle of Vatavyadhi Chikitsa. Treatment commenced with Rookshana, followed by Rooksha snigda and Snigda swedas externally. Gulgulutikthakam kashayam, Lakshadi gulgulu, Gulgulutikthakam ghrtham and Aswagandharasayanam were the internal medicines given. Dhanyakizhi, Lepanam, Jambeera pinda sweda and Patrapotala sweda were given as external therapy. Visual analogue scales for pain, range of movements, duration and severity of stiffness were used to evaluate the effectiveness of the treatment. Patient-reported outcome measures such as Hip disability and Osteoarthritis Outcome Score (HOOS), Lequesne Index were used to assess the quality of life of the patient. Significant improvement was noted in the VAS for the pain, duration and severity of stiffness. Range of movements and daily routine work ability also showed significant improvement. Although this particular case was krichrasadhya, it was effectively managed through Ayurvedic therapies, which shows its relevance in this current scenario that emphasises the invasive approaches.